Mandiri Pangan Plosokerep: Integrasi Kebun Mini, Edukasi Hortikultura dan Teknologi Ramah Lingkungan - Hartanti, Dyah Ayu Sri; Puspaningrum, Yessita; Aini, Nurul; Khiftiyah, Ana Mariatul; Fatahillah, Mohammad Roikhul; Baydlowi, Mohamad Mahfud; Huda, Rizqi Nurul (LPPM Universitas KH. A. Wahab Hasbullah, 2025)
Food security remains a critical challenge in rural communities with limited land resources. This community service program aimed to enhance household food independence in Plosokerep Village, Jombang, through the integration of mini gardens, organic horticulture education, and environmentally friendly technology. The program applied a participatory action research approach involving 60 households and three educational institutions. Activities included the distribution of vegetable seedlings, training on organic fertilizer and botanical pesticide production, and the establishment of demonstration gardens. Pre- and post-tests were conducted to measure knowledge improvement, while field observations assessed adoption rates and sustainability potential. Results showed a 71.9% increase in participants’ knowledge, a 92% plant survival rate, and the formation of informal farmer groups. The program also reduced household organic waste by 25% and pesticide use by 70%. These findings indicate that simple, community-based agricultural interventions can significantly improve food security, environmental awareness, and social cohesion, and can be replicated in other areas with similar conditions.